The Effect of 8 Weeks of Strength Training on Fluctuations of Neck-Shoulder Pain in Female Carpet Weavers - khadijeh afshin; Naser Behpoor (Sport Sciences and Health Research)
Nowadays musculoskeletal disorders are the most prevalent harmful factors in work environments. Non-ergonomic work stations and unsuitable designs of work environments confront workers with musculoskeletal disorders creating risk factors. It seems that the prevalence of these disorders in carpet weavers is more than other jobs. The aim of this study was to investigate the effect of strength training on neck-shoulder pain of female carpet weavers. This study was semi-experimental with a pretest and posttest design. The population consisted of 30-40-year-old female carpet weavers. 20 subjects whose intensity of pain on numerical rating scale was equal or more than 3 were randomly assigned to two control and experimental groups. After 8 weeks of strength training, the intensity of present‚ usual and worst pain was measured again by a 10-point scale. The comparison of pretest and posttest in the experimental group showed a significant difference in the intensity of present‚ usual and worst pain. This reduction was reported as %53‚ %50 and %58 for worst‚ usual and present pain respectively. But in control group, no significant differences were observed between pretest and posttest. According to these findings, special strength training reduced worst, usual and present pain.